A statistical study of Bay of Bengal disturbances ( 1961-80) using satellite imagery (MAUSAM, 1983)
With a view to understand the probable intensity of disturbances in the Bay of Bengal that are likely to occur during the various months of the year, a statistical study has been undertaken of depressions and storms during the period .1961 to 1980. As T-number classification according to Dvorak’s scale is available over India only from 1974, systems during the period 1961 to 1973 were converted to the corresponding T-numbers for the purpose of this study. The frequency distribution of the disturbances reveals the present of double maximum, one in May and the other in October. The modal curve suggests that while severe cyclonic storms occur In May, those with core of hurricance winds generally occur in November and December only.